Assessing the Genetic Relationship between Three Selected Species of Rauvolfia using Isoenzyme Profiles and Morphological Characters - Merlin Franco1, T. Renisheya Joy Jeba Malar, A. Usha Raja Nanthini2, M. Johnson1*, F. (Journal of Phytology, 2011)
Using Isoenzyme markers to study genetic diversity and relationship is the oldest and easiest method. In the current study, variation in Isozymic profiles as well as distinguishable morphological characters has been considered to reveal the genetic diversity and relationship existing between three species of Rauvolfia viz., Rauvolfia serpentina (L.) Benth. ex Kurz,Ã‚Â Rauvolfia micranthaÃ‚Â Hook. f. and Rauvolfia tetraphylla L. The enzymes selected for the study are Isoperoxidase, Isoesterasse, Acid Phosphatase, Alkaline Phosphatase and Poly phenol oxidase. The study shows that the species R. serpentina is distinct from R. micrantha and R. tetraphylla which show greater affinity towards each other.